Synergistic Regulation of Nitrogen and Sulfur on Redox Balance of Maize Leaves and Amino Acids Balance of Grains - Liu, Shuoran; Cui, Shuai; Zhang, Xue; Wang, Yin; Mi, Guohua; Gao, Qiang (Frontiers in Plant Science, 2020)
As the primary food crop, maize is widely grown around the world. However, the deficiency of essential amino acids such as lysine, tryptophan and methionine results in poor nutritional quality of maize. In addition, the protein concentration of maize declines with the increase of yield, which further reduces the nutritional quality. Here, the photosynthesis of leaves, grain amino acids composition and stoichiometry of N and S were explored. The results showed that N and S maintained the redox balance by increasing the content of glutathione in maize leaves, thereby enhancing the photosynthetic rate and maize yield. Simultaneously, the synergy of N and S increased the grain protein concentration and promoted amino acids balance by increasing the cysteine concentration in maize grains. The maize yield, grain protein concentration and the concentration of essential amino acids such as lysine, tryptophan and methionine could be simultaneously increased in the N : S ratio range of 11.0 to 12.0.Overall, the synergy of N and S simultaneously improved the maize yield and nutritional quality by regulating the redox balance of maize leaves and the amino acids balance of grains, which provided a new theoretical basis and practical method for sustainable production of maize.